Novel synthesis of coumarins employing triphenyl(alpha-carboxymethylene)-phosphorane imidazolide as a C-2 synthon - Upadhyay, Puspesh K.; Kumar, Pradeep (Tetrahedron Letters, 2009)
A novel one-pot synthesis of coumarins via intramolecular Wittig cyclization from the reaction of phenolic compounds containing ortho-carbonyl group and triphenyl(alpha-carboxy methylene)phosphorane imidazolide is described. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Carbonyldiimidazole; Coumarins; Intramolecular Wittig reaction; Phenolic compound; Phosphorane

Nucleophilic fluorination using imidazolium based ionic liquid bearing tert-alcohol moiety - Shinde, Sandip S.; Patil, Sunil N.; Ghatge, Amruta; Kumar, Pradeep (New Journal of Chemistry, 2015)